The impact of outdoor play on children’s well-being: A scoping review - Khairul Firdaus Ne'matullah; Nabilah Abd Talib; Rita Wong Mee Mee; Lim Seong Pek; Saturia Amiruddin; Md Rosli Ismail (Masyarakat, Kebudayaan dan Politik, 2022)
Outdoor play is a broad term that refers to a wide range of activities in a natural setting. However, modern technological advancements and gadgets such as television, computer and online games have resulted in children spending an increasing amount of time each day engaged in sedentary indoor activities rather than spending time outdoors. Many children’s social and physical health has deteriorated because of the reduction in outdoor access, which has been increasingly prevalent in recent years and may have long-term consequences. This scoping review aimed to determine what information was currently available on the impact of outdoor play on children’s wellbeing. This scoping review was conducted following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses Extension for Scoping Reviews (PRISMA-ScR) criteria. As many as 165 citations were discovered across six databases for this scoping review, and 13 articles were eligible for inclusion. The majority of the findings showed that outdoor play positively impacts children’s social, emotional, physical, and cognitive development.